Sleep in the intensive care unit: limiting elements of noise in the critical care environment (SILENCE) - Darbyshire, J (2019)
Introduction Sound levels in the intensive care unit (ICU) are persistently higher than World Health Organisation recommendations. This can lead to poor patient experiences including limited sleep, increased risk of delirium during admission, and prolonged recovery. Staff too can be affected. High noise levels are a distractor, can reduce concentration, and impair effective delivery of care.